A revision of the neotropical Mucuna species (Leguminosae—Papilionoideae) - Moura, Tânia M. De; Lewis, Gwilym P.; Mansano, Vidal F.; Tozzi, Ana M. G. A. (Phytotaxa, 2018)
The genus Mucuna comprises approximately 105 tropical and sub-tropical species, with the highest diversity occurring in the Paleotropics. In the Neotropics, 13 new species have been described recently and a number of regional floras have been published. A recent floristic treatment for Colombia has summarized the Mucuna species found in the Neotropics, but since then many new species and new geographical records have been published. A complete taxonomic treatment of all neotropical species and an identification key to all neotropical taxa is currently lacking. The aim of this study is to present a complete taxonomic account of the species of Mucuna occurring in the Neotropics. Descriptions of 25 taxa (24 species and one variety) are included in the treatment, including type specimen details, synonymy, illustrations, distribution maps, and preliminary conservation assessments for each species, together with a species identification key.